If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying lnx + -2lnx = 3 Combine like terms: lnx + -2lnx = -1lnx -1lnx = 3 Solving -1lnx = 3 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Divide each side by '-1nx'. l = -3n-1x-1 Simplifying l = -3n-1x-1
| 6x-4=20x+3 | | 6x-23+x+54=180 | | 4x+2x(x+4)= | | -4x-6(-2+4)=64 | | 2x+y-z=7z | | -4x-6(-2+4)=64 | | 3x-1=-3x+3 | | 3x-1=-3x+3 | | -5x+-2=-2X+4 | | -6x-5(-3x-3)=60 | | 114=2x+3x | | 5x+7y=3890 | | 8x+7y-5-5x+6y-3= | | -2x-2(-5x-4)=-80 | | 15+4y-1=15y-13-2y | | y+(y-2)2=2 | | 3x-n=7+n | | 25-13=3(x-1) | | -13.9=b+17.1 | | r+7= | | 15-44=3(x-4)-5 | | 3x+(x-5)=15+4 | | -16+13=m-2 | | -3x=8-(-1) | | 3w+5-2w+7= | | 2x^6=-3 | | 5mn-2m(m-2n)= | | 7(x+2)-3x=4(x-1)+10 | | -13.9=b-17.1 | | 3(2n-m)+4m= | | -9x+7=16 | | 9X-2(8-X)=61 |